Fc galactosylation follows consecutive reaction kinetics and enhances immunoglobulin G hexamerization for complement activation. Issue 1 (1st January 2021) - Wei, Bingchuan; Gao, Xuan; Cadang, Lance; Izadi, Saeed; Liu, Peilu; Zhang, Hui-Min; Hecht, Elizabeth; Shim, Jeongsup; Magill, Gordon; Pabon, Juan Rincon; Dai, Lu; Phung, Wilson; et al.
ABSTRACT: Fc galactosylation is a critical quality attribute for anti-tumor recombinant immunoglobulin G (IgG)-based monoclonal antibody (mAb) therapeutics with complement-dependent cytotoxicity (CDC) as the mechanism of action. Although the correlation between galactosylation and CDC has been known, the underlying structure–function relationship is unclear. Heterogeneity of the Fc N-glycosylation produced by Chinese hamster ovary (CHO) cell culture biomanufacturing process leads to variable CDC potency. Here, we derived a kinetic model of galactose transfer reaction in the Golgi apparatus and used this model to determine the correlation between differently galactosylated species from CHO cell culture process. The model was validated by a retrospective data analysis of more than 800 historical samples from small-scale and large-scale CHO cell cultures. Furthermore, using various analytical technologies, we discovered the molecular basis for Fc glycan terminal galactosylation changing the three-dimensional conformation of the Fc, which facilitates the IgG1 hexamerization, thus enhancing C1q avidity and subsequent complement activation. Our study offers insight into the formation of galactosylated species, as well as a novel three-dimensional understanding of the structure–function relationship of terminal galactose to complement activation in mAb therapeutics.